Cerebral amyloid angiopathy, cerebral microbleeds and implications for anticoagulation decisions: The need for a balanced approach. Issue 2 (February 2018) - Charidimou, Andreas; Shoamanesh, Ashkan; Al-Shahi Salman, Rustam; Cordonnier, Charlotte; Perry, Luke A; Sheth, Kevin N; Biffi, Alessandro; Rosand, Jonathan; Viswanathan, Anand
Cerebral amyloid angiopathy is a common hemorrhagic small vessel disease of the brain, often associated with high risk of spontaneous lobar intracerebral hemorrhage. When the suspicion of cerebral amyloid angiopathy is raised, clinicians are hesitant in prescribing oral anticoagulation in patients in whom it is otherwise indicated, including the case of non-valvular atrial fibrillation. This is one of the thorniest clinical dilemmas in the field currently. In this short Leading Opinion piece by an international panel of clinicians-researchers active in the field, we present our consistent approach and future outlook on oral anticoagulation post intracerebral hemorrhage and in the setting of clinical-radiologic evidence of cerebral amyloid angiopathy. We discuss recent advances and support a more balanced approach with implications for the wider neurological clinical community in regards to successful recruiting this patient population in ongoing and future randomized trials.